Validity of evidence-derived criteria reactive attachment disorder: indiscriminately social/disinhibited and emotionally withdrawn/inhibited types - Gleason, Mary Margaret (2011)
OBJECTIVE: In this study, we examine the validity of criteria for indiscriminately social/disinhibited and emotionally withdrawn/inhibited RAD. METHODS: As part of a longitudinal intervention trial of previously institutionalized children, caregiver interviews and direct observational measures provided continuous and categorical data used to examine the internal consistency, criterion validity, construct validity, convergent and discriminant validity, association with functional impairment, and the stability of these disorders over time. RESULTS: Our findings, like those in other studies, show distinctions between the two types of RAD. Evidence-derived criteria for both types of RAD showed acceptable internal consistency and criterion validity. In this study, rates of the indiscriminately social/disinhibited RAD at baseline, 30 months, 42 months, and 54 months were 41/129 (31.8 %), 22/122 (17.9%), 22/122 (18.0%), and 22/125 (17.6%), respectively. Signs of indiscriminately social/disinhibited RAD showed little association with caregiving quality. Nearly half of children with indiscriminately social/disinhibited RAD had organized attachment classifications. Signs of indiscriminately social/disinhibited RAD were associated with signs of activity/impulsivity and of ADHD and modestly to inhibitory control, but were distinct from the diagnosis of ADHD. At baseline, 30, 42, and 54 months, 6/130 (4.6%), 4/123 (3.3%), 2/125(1.6%), and 5/122 (4.1%) of children met criteria for emotionally withdrawn/inhibited RAD. Emotionally withdrawn/inhibited RAD was moderately associated with caregiving at the first three time points and strongly associated with attachment security. Signs of this type of RAD were associated with depressive symptoms, although two of the five children with this type of RAD at 54 months did not meet criteria for major depressive disorder. Signs of both types of RAD contributed independently to functional impairment and were stable over time. CONCLUSIONS: Evidence-derived criteria for indiscriminately social/disinhibited and emotionally withdrawn/inhibited RAD define two statistically and clinically cohesive syndromes that are distinct from each other, shows stability over 2 years, have predictable associations with risk factors and attachment, can be distinguished from other psychiatric disorders, and cause functional impairment.